Security challenges in the South Asian Region - Sirina , Yelyzaveta (Young Scholars Grinchenko – Seton International Journal, 2025)
The South Asian Region has become a significant center for security studies, as it has witnessed numerous interstate conflicts, centers of international terrorism, separatism, and political instability, as well as the presence of nuclear-armed states in the region. South Asia represents the growing role of the security factor and the problem of building a regional security system. The study highlights security problems in South Asia, existing mechanisms to counter them, future development prospects, and lessons for Ukraine.